2017
DOI: 10.2139/ssrn.3089498
|View full text |Cite
|
Sign up to set email alerts
|

Regulation by Catastrophe Insurance for Climate Risks: A Comparative Study

Abstract: Under the influence of climate-related extremes, the world is exposed to more and more catastrophe risks. Increasingly it is held that the government alone may not be able to adequately prevent disaster risks; a combination of public and private regulation is therefore warranted. Regulation via insurance may help to realize the goal of disaster risk reduction and to mitigate the corresponding losses. In this article we identify five regulatory toolsrisk-based pricing, contract design, loss prevention services,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The insurers normally base their decision on data obtained from weather station to check the wind speed. A similar study by He and Faure (2017) in United Kingdom showed that there are multiple insurance companies specialized in the greenhouse sector and offers a professional programme of property damage and loss of income insurance. Such insurance package grants comprehensive cover to the horticultural sector throughout United Kingdom (He et al, 2017).…”
Section: Literature Review Capacity Building For Agriculture Insuranc...mentioning
confidence: 90%
See 2 more Smart Citations
“…The insurers normally base their decision on data obtained from weather station to check the wind speed. A similar study by He and Faure (2017) in United Kingdom showed that there are multiple insurance companies specialized in the greenhouse sector and offers a professional programme of property damage and loss of income insurance. Such insurance package grants comprehensive cover to the horticultural sector throughout United Kingdom (He et al, 2017).…”
Section: Literature Review Capacity Building For Agriculture Insuranc...mentioning
confidence: 90%
“…A similar study by He and Faure (2017) in United Kingdom showed that there are multiple insurance companies specialized in the greenhouse sector and offers a professional programme of property damage and loss of income insurance. Such insurance package grants comprehensive cover to the horticultural sector throughout United Kingdom (He et al, 2017). These insurance firms insure horticultural producers and retail nurseries and offer support in the event of a claim depending on the plant, equipment and the risk situation.…”
Section: Literature Review Capacity Building For Agriculture Insuranc...mentioning
confidence: 90%
See 1 more Smart Citation
“…Also, for other types of disasters, comprehensive (mandatory) coverage has been advocated to deal with low demand due to cognitive and informational problems (Kunreuther 1968 ). Several countries, including France, Belgium, Norway and Spain, have now introduced such a mandatory compensation system for (particular) natural catastrophes (see further He and Faure 2018 ). Mandatory coverage therefore undoubtedly has the advantage of curing adverse selection by including all risks (good and bad) into the mandatory system; via premium and risk differentiation the moral hazard problem could be cured as well, “Only when government requires the purchase of insurance directly or indirectly, or when insurers adopt coverage terms akin to paradigmatic command-and-control regulation, does it make sense to label these techniques ‘regulation’” (Abraham and Schwarcz 2023 ).…”
Section: Possible Solutions Within the Legal Frameworkmentioning
confidence: 99%